Impact of Climatic and Environmental Factors on the Distribution of Sitotroga Cerealella (Olivier) and Sitophilus Oryzae (Linnaeus) in Benin. - Togola, Abou; Nwilene, Francis E.; Hell, Kerstin; Oyetunji, Olumuye E.; CHOUGOUROU, CHÈPO DANIEL (My University, 2014)
Angoumois grain moth (Sitotroga cerealella (Olivier)) and rice weevil (Sitophilus oryzae (Linnaeus)) are devastating pests of stored cereals throughout the world. This study aims to establish the effect of the climatic and environmental factors on the distribution and infestation source of these two species in Benin. For the purpose, 138 farmers’ rice stocks were monitored and sampled in 52 locations throughout the country. At each location, pest populations were monitored in storage, in rice fields and in the natural habitat. The monitoring methods comprised visual observation, monitoring of harvested panicles for the emergence of adults and use of sex pheromone or aggregation traps. During the inspection, parameters such as relative humidity, temperature, and grain moisture content were measured. Finally, collected rice samples were taken to the laboratory to identify insect species and count the number of individuals. Both species occurred at high population densities in the southern and central regions of the country where average temperatures (30.42 ºC to 31.2 ºC) and high humidity (85.2% to 76.8 %) prevailed. However, in the northern region, the densities of these species were very low due to the dry weather conditions of the region. Angoumois grain moth was observed in paddy fields and warehouses, and its initial infestations were observed at rice maturation. Rice weevil was mostly observed in the storage areas; it was less frequent in paddy fields. These results helped to identify the distribution and the potential habitats of these two species in relation to the climatic conditions of the surveyed ecozones and the moisture content of stored grain.
Keywords: Habitats; Geographic regions; Initial infestation; Sitotroga cerealella; Sitophilus oryzae